Integrating Qur'an-Based Eclectic Methods in Arabic Language Education: A Theoretical and Practical Framework - Moh Aman; Husnul Amin (STAI Hubbulwathan Duri, 2025)
Arabic language education in Islamic institutions is expected to achieve linguistic competence while remaining aligned with Qur’anic educational values. Yet, instruction often oscillates between traditional form-focused practices and contemporary communicative demands without a clear integrative framework. This study aims to conceptualize a Qur’an-based eclectic approach that aligns selected second/foreign language teaching methods with key Qur’anic pedagogical principles.Using a library-based qualitative content analysis, the study reviewed classical Islamic educational works and contemporary scholarship on Arabic language pedagogy and eclectic methodology (2010–2024, with classical sources as foundational references). Sources were thematically coded to identify (1) core Qur’anic educational values and (2) compatible eclectic teaching strategies, then synthesized into an integrative framework.Findings indicate that Qur’anic principles—particularly hikmah (wisdom), mau‘izah hasanah (benevolent counsel), mujādalah (respectful dialogue), tadabbur (deep reflection), and tazkiyah (self-purification)—can be pedagogically operationalized through blended strategies such as guided textual contemplation, narrative-based learning, reflective journaling, dialogic debate, scaffolding for grammar–vocabulary development, and collaborative tasks. The resulting model connects values, teaching strategies, and learning outcomes across cognitive, affective, and psychomotor domains, positioning Arabic learning as both language development and character formation.This conceptual synthesis suggests that a Qur’an-based eclectic framework may enhance instructional coherence in Islamic settings by balancing communicative effectiveness with ethical-spiritual aims. Further empirical studies are recommended to test the model’s feasibility and impact in classroom practice.